Acute Intraoperative Hypoxemia During Right Pneumonectomy—The Heart and Lung Interaction: A Case Report. Issue 4 (April 2021) - Barragan-Bradford, Diana; Gaissert, Henning; Vidal Melo, Marcos F.
Abstract : A 75-year-old woman with a history of right-upper lobectomy for adenocarcinoma presented for a right completion pneumonectomy due to 2 new fluorodeoxyglucose-avid densities on the remaining lung. After uneventful anesthetic induction and surgical resection with modest blood loss, the patient developed refractory hypoxemia on emergence without significant hemodynamic changes. Despite delivery of fraction of inspired oxygen (Fio2 ) = 1.0, confirmed position of the double-lumen tube, and exclusion of common causes of hypoxemia, hypoxemia persisted. An emergent transesophageal echocardiogram revealed a significant intracardiac shunt due to a patent foramen ovale. Specific cardiorespiratory management to achieve a positive left-right heart pressure gradient resulted in prompt normoxemia and successful extubation. Abstract : Supplemental Digital Content is available in the text.